Health system responsiveness: a systematic evidence mapping review of the global literature - Gadija Khan; Nancy Kagwanja; Eleanor Whyle; Lucy Gilson; Sassy Molyneux; Nikki Schaay; Benjamin Tsofa; Edwine Barasa; Jill Olivier (BMC, 2021)
Abstract Background The World Health Organisation framed responsiveness, fair financing and equity as intrinsic goals of health systems. However, of the three, responsiveness received significantly less attention. Responsiveness is essential to strengthen systems' functioning; provide equitable and accountable services; and to protect the rights of citizens. There is an urgency to make systems more responsive, but our understanding of responsiveness is limited. We therefore sought to map existing evidence on health system responsiveness. Methods A mixed method systemized evidence mapping review was conducted. We searched PubMed, EbscoHost, and Google Scholar. Published and grey literature; conceptual and empirical publications; published between 2000 and 2020 and English language texts were included. We screened titles and abstracts of 1119 publications and 870 full texts. Results Six hundred twenty-one publications were included in the review. Evidence mapping shows substantially more publications between 2011 and 2020 (n = 462/621) than earlier periods. Most of the publications were from Europe (n = 139), with more publications relating to High Income Countries (n = 241) than Low-to-Middle Income Countries (n = 217). Most were empirical studies (n = 424/621) utilized quantitative methodologies (n = 232), while qualitative (n = 127) and mixed methods (n = 63) were more rare. Thematic analysis revealed eight primary conceptualizations of 'health system responsiveness', which can be fitted into three dominant categorizations: 1) unidirectional user-service interface; 2) responsiveness as feedback loops between users and the health system; and 3) responsiveness as accountability between public and the system. Conclusions This evidence map shows a substantial body of available literature on health system responsiveness, but also reveals evidential gaps requiring further development, including: a clear definition and body of theory of responsiveness; the implementation and effectiveness of feedback loops; the systems responses to this feedback; context-specific mechanism-implementation experiences, particularly, of LMIC and fragile-and conflict affected states; and responsiveness as it relates to health equity, minority and vulnerable populations. Theoretical development is required, we suggest separating ideas of services and systems responsiveness, applying a stronger systems lens in future work. Further agenda-setting and resourcing of bridging work on health system responsiveness is suggested.